Experimental evaluation of energy consumption in machine tools: a case study for a two-spindle turning center - Pelegrino, Danilo Henrique; dos Santos, Raphael Galdino; Coelho, Reginaldo Teixeira (Journal of the Brazilian Society of Mechanical Sciences and Engineering, 2019)
To deal with a constant energy rising prices and significant demands for minimizing environmental impacts related to the electricity generation using fossil fuels, the theme “energy consumption” has brought a plenty of discussion onto the agenda of manufacturing industries nowadays. Therefore, the reduction in energy consumption in manufacturing processes is a fundamental issue for the industrial segment at the present time. Such subject requires knowledge about the energy requirements from machines and all involved peripheral equipment. Although the machining processes have always been the subject of several researches and studies, energy analysis has become a relatively new topic, as well as “energy efficiency”. To improve energy efficiency in machining processes particularly in machine tools (MTs), energy consumption data must be obtained to help in process planning and also contribute to improve the efficiency of machines, as a whole. Moreover, to meet growing market demand for more efficient machines and global competitiveness in the manufacturing sector, MT manufacturers are facing major challenges to improve productivity and reduce energy consumption. Considering the increasing energy demands and industrial sustainability, the present research presents a detailed study of energy consumption in a two-spindle turning center and suggests strategies to reduce energy consumption in MTs as a whole. The results obtained, so far, indicates that optimizing the operational behavior of MTs through smart operation modes, by adapting the power demand to the current production requirements, seems to be a good procedure to reduce the amount of energy consumed. It also makes the processes and machines more efficient and improves environmental performance of machining processes, in general.